Learning English through International Student Exchange Programs: English Education Department Students’ Voices - Suryanto Suryanto; Betha Labova Ayuza; Noor Ahnis Othman (Journal of Foreign Language Teaching and Learning, 2022)
English language learning is a process that students must go through in order to reach the optimum level of proficiency in the language. International student exchange programs are activities that might assist students in practicing and improving their English. The purposes of this study were to investigate the benefits and to identify the challenges of participating in an international student exchange program while studying English at the English Language Education Department of an Islamic Private University in Yogyakarta. The research design for this study was a qualitative descriptive one. The data for this study were gathered through interviews.  Three students from the English Language Education Department of a private Islamic university in Yogyakarta participated in this investigation. The first finding concerned the advantages of participating in an international student exchange program while studying English. It shown that participating in international student exchange programs aided students in making foreign friends, interacting with native English speakers, practicing, and improving their English abilities, and boosting their self-confidence. The second result concerned the challenges associated with participating in an international student exchange program to improve their English. It demonstrated that students who participated in an international student exchange program failed to engage with local people outside of school and experienced culture shock. All associated parties, including students, host universities, university senders, and the program's committee, should organize and execute the program's activities with care and attention, beginning with the program's planning, preparation, deployment, evaluations, and follow-up.